Anatomy and biomechanics of gluteus maximus and the thoracolumbar fascia at the sacroiliac joint. Issue 2 (20th August 2013) - Barker, P.J.; Hapuarachchi, K.S.; Ross, J.A.; Sambaiew, E.; Ranger, T.A.; Briggs, C.A.
<x xml:space="preserve">Abstract</x> Biomechanical models predict that recruitment of gluteus maximus (GMax) will exert a compressive force across the sacroiliac joint (SIJ), yet this muscle requires morphologic assessment. The aims of this study were to document GMax's proximal attachments and assess their capacity to generate forces including compressive force at the SIJ. In 11 embalmed cadaver limbs, attachments of GMax crossing the SIJ were dissected and their fascicle orientation, length and attachment volume documented. The physiological cross‐sectional area (PCSA) of each attachment was calculated along with its estimated maximum force at the SIJ and lumbar spine. GMax fascicles originated from the gluteus medius fascia, ilium, thoracolumbar fascia, erector spinae aponeurosis, sacrum, coccyx, dorsal sacroiliac and sacrotuberous ligaments in all specimens. Their mean fascicle orientation ranged from 32 to 45° below horizontal and mean length from 11 to 18 cm. The mean total PCSA of GMax was 26 cm2 (range 16–36), of which 70% crossed the SIJ. The average maximum force predicted to be generated by GMax's total attachments crossing each SIJ was 891 N (range 572–1, 215), of which 70% (702 N: range 450–1, 009) could act perpendicular to the plane of the SIJ. The capacity of GMax to generate an extensor moment at lower lumbar segments was estimated at 4 Nm (range 2–9.5). GMax may generate compressive forces at the SIJ through its bony and fibrous attachments. These may assist effective load transfer between lower limbs and trunk. Clin. Anat. 27:234–240, 2014. © 2013 Wiley Periodicals, Inc.